The Effect of a Program Based on Educational Games with Extra-Curricular Activities in Developing Some Life Skills for Children with Autism - Haunaz Ali Ahmed; Afrah Yassin Mohamed (Zanco Journal of Humanity Sciences)
Building a training program based on educational games with extra-curricular activities in developing life skills for children with autism disorder.